Lehman Brothers research : an analyst decides that the market overreacted to Merck's Vioxx woes - Hutchins, Spencer, (SAGE knowledge. Cases., 2016)
In September 2004, Merck announced a voluntary withdrawal of Vioxx, one of its top earning drugs, after a new study suggested that it increased the risk of heart attacks. In only a few days, Merck's share price collapsed, and nearly $25 billion in shareholder wealth was erased. This case examines the market reaction to Merck's product recall.